Developing a New Shock‐Collar Design for Safe and Efficient Use on Wild Wolves. (7th May 2013) - Hawley, Jason E.; Rossler, Shawn T.; Gehring, Thomas M.; Schultz, Ronald N.; Callahan, Peggy A.; Clark, Raymond; Cade, Jerry; Wydeven, Adrian P.
Abstract Electronic training collars, or shock collars, have received relatively little application as a non‐lethal management tool for reducing livestock losses caused by gray wolves (Canis lupus). One of the major obstacles to using shock collars on wolves has been the lack of a safe and efficient collar design. We developed a new shock‐collar design and tested it for safety and efficacy on captive wolves. Our design used a radiocollar with a shock unit mounted on the back. Shock units were fitted with rounded probes that contact the back of a wolf's shaved neck and with externally mounted batteries to increase battery life. We tested our design in 5 different captive trials conducted during 2003–2005 at the Wildlife Science Center, Minnesota, USA, and eliminated neck damage shown in previous shock‐collar research, while retaining the ability to effectively deliver a shock. We extended battery life to 80 days. We believe this new shock‐collar design could be used as a safe and efficient alternative to lethal control in certain situations for wild wolves. © 2013 The Wildlife Society.